Managing manufacturing knowledge in Europe in the era of industry 4.0 - Patalas-Maliszewska, Justyna (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Manufacturing companies need to adapt to the requirements of functioning in the era of Industry 4.0 and major technological disruptions. The use of knowledge-based decision support tools has also become necessary in order for enterprises to survive in a competitive environment. This book offers a new approach to designing the knowledge management process and integrating it with the implementation of Industry 4.0 technology. The book presents the methods used in a customer-oriented organization under the Management of Manufacturing Knowledge (M-Know Process). More specifically, methods for defining and collecting customer requirements are presented and methods on how to receive manufacturing knowledge, as well as how to formalise the acquired knowledge using key technologies of Industry 4.0, are discussed. The author also presents real case studies from western and central Europe and offers recommendations for the production manager. The instrumentation of methods and tools to support knowledge management, in the production of individualised products presented therein, will allow the manufacturing company to be transformed digitally, into a customer-oriented organisation operating in accordance with the assumptions of Industry 4.0. This book will be a valuable read for production researchers, academicians, PhD students and postgraduate level students of industrial engineering and industrial management. The practical case studies will also make the book a useful resource for managers of manufacturing enterprises"--
OCLC-licensed vendor bibliographic record.
Keywords: Manufacturing industries -- Europe -- Management; Production management -- Europe; Knowledge management -- Europe; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Information Management